2017
DOI: 10.1007/s13361-017-1798-5
|View full text |Cite
|
Sign up to set email alerts
|

Ion Mobility Spectrometry-Mass Spectrometry Coupled with Gas-Phase Hydrogen/Deuterium Exchange for Metabolomics Analyses

Abstract: Ion mobility spectrometry-mass spectrometry (IMS-MS) in combination with gas-phase hydrogen/deuterium exchange (HDX) and collision-induced dissociation (CID) is evaluated as an analytical method for small-molecule standard and mixture characterization. Experiments show that compound ions exhibit unique HDX reactivities that can be used to distinguish different species. Additionally, it is shown that gas-phase HDX kinetics can be exploited to provide even further distinguishing capabilities by using different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…Under mild conditions, the number of exchanges can be predicted if the structure of the molecule (SMILES or SMARTS) is known. Thus, by applying modern tools of chemical informatics, the number of exchanges observed experimentally for unknown molecules can be used as a structural descriptor or filter parameter when performing a database search. , …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Under mild conditions, the number of exchanges can be predicted if the structure of the molecule (SMILES or SMARTS) is known. Thus, by applying modern tools of chemical informatics, the number of exchanges observed experimentally for unknown molecules can be used as a structural descriptor or filter parameter when performing a database search. , …”
mentioning
confidence: 99%
“…Thus, by applying modern tools of chemical informatics, the number of exchanges observed experimentally for unknown molecules can be used as a structural descriptor or filter parameter when performing a database search. 11,12 The first hydrogen/deuterium (H/D) and 16 O/ 18 O isotopic exchange reactions were observed by Lewis in 1933. 13,14 Simply dissolving the sample in D 2 O instead of H 2 O leads to the instant exchange of protons from all functional groups such as −OH, −COOH, −NH, and −SH.…”
mentioning
confidence: 99%
“…: 943.68) (only observed during fragmentation of a‐I ) after desorption of the produced CO 2 (Figure 3 a and Figure 4). Other peaks were ascribed to a cation exchange reaction in the gas phase that commonly occur during ESI‐MS experiments [25] . Reaction of a‐I at relatively low collision energy indicated that the reaction barrier towards the oxygen vacant species was low.…”
Section: Resultsmentioning
confidence: 99%
“…Other peaks were ascribed to ac ation exchange reaction in the gas phase that commonly occur during ESI-MS experiments. [25] Reaction of a-I at relatively low collision energy indicated that the reaction barrier towards the oxygen vacant species was low.W hent he solution was treated with CO for 1h,the previously observed species (a-I)disappeared and two species: + H + + K + } 2À (a-III/a-IV,calc. : 1432.06, expt.…”
Section: àmentioning
confidence: 99%